Silicon-carbon / graphite composite negative electrode and lithium ion battery based on multi-parameter coupling optimization
Patent Information
- Application Number
- CN202610683624.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-18
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]然而,硅碳材料的引入带来了一系列挑战:硅在充放电过程中体积膨胀巨大,导致电极结构破坏、循环性能恶化;硅本身导电性差,影响倍率性能
本发明提供了一种基于多参数耦合优化的硅碳/石墨复合负极,将多个参数包括:碳硅的质量分数、碳硅材料中硅元素的质量分数、负极材料中单壁碳纳米管的质量分数、石墨的中值粒径、硅碳材料的中值粒径耦合到“倍率性能”和“循环寿命”这两个核心指标中,同时设定倍率性能因子和循环寿命因子的阈值不仅能够快速、高效地获得硅碳/石墨复合负极的最佳的材料参数组合,极大地缩短了研发周期,而且同时确保锂离子电池的倍率性能和循环寿命。
Smart Images

Figure QLYQS_1 
Figure QLYQS_9 
Figure SMS_108
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a silicon-carbon / graphite composite anode and lithium-ion battery based on multi-parameter coupling optimization. Background Technology
[0002] Currently, commercially available graphite anode material has a theoretical specific capacity of only 372 mAh / g, which cannot meet the requirements of large-scale energy storage systems. Incorporating high-capacity silicon-carbon materials into graphite anodes can improve the energy density of lithium-ion batteries.
[0003] However, the introduction of silicon-carbon materials has brought a series of challenges: silicon expands greatly in volume during charging and discharging, which leads to the destruction of electrode structure and deterioration of cycle performance; silicon itself has poor conductivity, which affects rate performance.
[0004] Currently, the problems of poor cycle stability and low rate performance are usually addressed by empirically setting single value ranges for each component (such as silicon-carbon ratio, silicon content, and amount of conductive agent added). However, this empirical "trial and error" method has obvious drawbacks: the formulation development cycle is long and the cost is high; and most importantly, it cannot guarantee that excellent cycle performance and rate performance can be obtained simultaneously within the set wide range. Summary of the Invention
[0005] To overcome the above problems, the present invention provides a silicon-carbon / graphite composite anode and a lithium-ion battery based on multi-parameter coupling optimization.
[0006] To achieve the above technical objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a silicon-carbon / graphite composite anode based on multi-parameter coupling optimization, comprising an anode current collector and an anode material loaded on one or both sides of the anode current collector. The negative electrode material includes an active material, a conductive agent, and a binder; The active substances include silicon carbide materials and graphite; The conductive agent is a single-walled carbon nanotube (SWCNT). Meanwhile, by comparing the rate performance factor and cycle life factor calculated from the mass fraction of carbon silicon in the active material, the mass fraction of silicon in the carbon silicon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size (D50) of graphite, and the median particle size (D50) of silicon-carbon material with the set threshold, the mass fraction or median particle size is optimized.
[0007] In one or more embodiments, the negative electrode current collector includes aluminum foil, copper foil, and titanium mesh, preferably copper foil.
[0008] In one or more embodiments, the adhesive includes one or more of polyacrylic acid, sodium alginate, polyimide, sodium carboxymethyl cellulose (CMC) / styrene-butadiene rubber (SBR) composite systems, preferably sodium carboxymethyl cellulose / styrene-butadiene rubber composite systems.
[0009] In one or more embodiments, the mass ratio of the active material, the conductive agent, and the binder is (94~98):(1~2):(2~3), preferably 96:1.5:2.5.
[0010] In one or more embodiments, the formula for calculating the rate performance factor using the mass fraction of carbon silicon in the active material, the mass fraction of silicon in the carbon silicon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size (D50) of graphite, and the median particle size (D50) of the silicon-carbon material is as follows: ; in, Indicates the rate performance factor; The mass fraction of carbon and silicon in the active material is 0. <A≤0.20; B represents the mass fraction of silicon in the silicon-carbon material, where 0.35 ≤ B ≤ 0.65. The value represents the mass fraction of single-walled carbon nanotubes in the negative electrode material, and 0.0004 ≤ C ≤ 0.001. The median particle size (D50) of graphite is given, and 5 μm ≤ Dg ≤ 15 μm. The median particle size (D50) of silicon-carbon materials is 3 μm ≤ ≤10 μm.
[0011] In one or more embodiments, the threshold value for the rate performance factor is set to 2000~8000.
[0012] In one or more embodiments, the formula for calculating the cycle life factor using the mass fraction of carbon silicon in the active material, the mass fraction of silicon in the carbon silicon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size (D50) of graphite, and the median particle size (D50) of the silicon-carbon material is as follows: ; in, Indicates the cycle life factor; The mass fraction of carbon and silicon in the active material is 0. <A≤0.20; B represents the mass fraction of silicon in the silicon-carbon material, where 0.35 ≤ B ≤ 0.65. The value represents the mass fraction of single-walled carbon nanotubes in the negative electrode material, and 0.0004 ≤ C ≤ 0.001. The median particle size (D50) of graphite is given, and 5 μm ≤ Dg ≤ 15 μm. The median particle size (D50) of silicon-carbon materials is 3 μm ≤ ≤10 μm.
[0013] In one or more embodiments, the set threshold for the cycle life factor is 1.5 to 4.0.
[0014] In one or more embodiments, the graphite includes one or more of artificial graphite and natural graphite.
[0015] A second aspect of the present invention provides a lithium-ion battery comprising the silicon-carbon / graphite composite anode described in the second aspect based on multi-parameter coupling optimization.
[0016] The beneficial effects of this invention are as follows: This invention provides a silicon-carbon / graphite composite anode based on multi-parameter coupling optimization. Multiple parameters, including the mass fraction of silicon-carbon, the mass fraction of silicon in the silicon-carbon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size of graphite, and the median particle size of the silicon-carbon material, are coupled to the two core indicators of "rate performance" and "cycle life." Simultaneously setting thresholds for both the rate performance factor and the cycle life factor not only allows for the rapid and efficient acquisition of the optimal material parameter combination for the silicon-carbon / graphite composite anode, significantly shortening the R&D cycle, but also ensures both the rate performance and cycle life of the lithium-ion battery. Detailed Implementation
[0017] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0018] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0019] Incorporating high-capacity silicon-carbon materials into graphite anodes can improve the energy density of lithium-ion batteries, but it also leads to problems such as poor cycle stability and low rate performance.
[0020] Currently, the problems of poor cycle stability and low rate performance are usually addressed by empirically setting a single range of values for each component (such as silicon-carbon ratio, silicon content, and amount of conductive agent added). However, this empirical "trial and error" method has obvious drawbacks: the formulation development cycle is long and the cost is high; and most importantly, it cannot guarantee that optimal cycle performance and rate performance can be obtained simultaneously within the set wide range.
[0021] This invention provides a silicon-carbon / graphite composite anode based on multi-parameter coupling optimization. Multiple parameters, including the mass fraction of silicon-carbon, the mass fraction of silicon in the silicon-carbon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size of graphite, and the median particle size of the silicon-carbon material, are coupled to the two core indicators of "rate performance" and "cycle life." Simultaneously setting thresholds for both the rate performance factor and the cycle life factor not only allows for the rapid and efficient acquisition of the optimal material parameter combination for the silicon-carbon / graphite composite anode, significantly shortening the R&D cycle, but also ensures both the rate performance and cycle life of the lithium-ion battery.
[0022] The formula for calculating the rate performance factor, which is derived from the mass fraction of carbon and silicon in the active material, the mass fraction of silicon in the carbon-silicon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size of graphite, and the median particle size of silicon-carbon material, is as follows: ; in, Indicates the rate performance factor; The mass fraction of carbon and silicon in the active material is 0. <A≤0.20; B represents the mass fraction of silicon in the silicon-carbon material, where 0.35 ≤ B ≤ 0.65. The value represents the mass fraction of single-walled carbon nanotubes in the negative electrode material, and 0.0004 ≤ C ≤ 0.001. The median particle size (D50) of graphite is given, and 5 μm ≤ Dg ≤ 15 μm. The median particle size (D50) of silicon-carbon materials is 3 μm ≤ ≤10 μm.
[0023] Mass fraction of carbon and silicon in active materials Mass fraction of silicon element in silicon-carbon materials It is a provider of high-rate performance; therefore, the numerator of the rate performance factor RF is × Silicon is key to improving energy density; however, the higher its proportion, the more severe the volume expansion and structural instability of the material, which in turn impairs rate performance, making it a "high-risk" variable. The mass fraction of single-walled carbon nanotubes in the anode material... Median particle size of graphite Median particle size of silicon-carbon materials It is a high-rate performance restorer: the denominator of the rate performance factor RF is To offset the negative impact of the aforementioned "high-risk" variables, it is necessary to increase the mass fraction of the high-performance conductive agent SWCNT (single-walled carbon nanotubes). The larger the value, the smaller the rate performance factor (RF) value, indicating that more conductive agent is needed to build a high-quality conductive network; at the same time, the closer the particle size of graphite and silicon carbide, the more uniform the electrode stacking, and the less damage to rate performance.
[0024] Setting the threshold for the rate performance factor to 2000-8000 better balances the four objectives of energy density, rate performance, cycle stability, and cost control, making it the optimal choice for overall performance.
[0025] A rate performance factor (RF) below 2000 may result in poor rate performance. To achieve a low RF, high-capacity materials (A, B) are sacrificed, leading to insufficient total active material and directly limiting the upper limit of energy density. This may result in greater reliance on expensive conductive agents (high-performance conductive agent SWCNT) or stringent particle size requirements, leading to increased costs or significantly increased processing difficulty.
[0026] With a rate performance factor (RF) exceeding 8000, the cycle life is significantly shortened. Problems such as drastic volumetric failure due to high carbon silicon content, increased internal resistance due to increased silicon content, and uneven electrode structure caused by excessive particle size differences will all occur simultaneously. These factors combined lead to rapid capacity decay during battery cycling, increasing the risk of failure.
[0027] The formula for calculating the cycle life factor using the mass fraction of carbon and silicon in the active material, the mass fraction of silicon in the carbon-silicon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size (D50) of graphite, and the median particle size (D50) of silicon-carbon material is as follows: ; in, Indicates the cycle life factor; The mass fraction of carbon and silicon in the active material is 0. <A≤0.20; B represents the mass fraction of silicon in the silicon-carbon material, where 0.35 ≤ B ≤ 0.65. The value represents the mass fraction of single-walled carbon nanotubes in the negative electrode material, and 0.0004 ≤ C ≤ 0.001. The median particle size (D50) of graphite is given, and 5 μm ≤ Dg ≤ 15 μm. The median particle size (D50) of silicon-carbon materials is 3 μm ≤ ≤10 μm.
[0028] To achieve the ideal cycle life, multiple parameters are coupled and optimized by adjusting the material ratio and particle size distribution. The core logic of the cycle life factor is to use a larger stable graphite phase (larger molecules) to "balance" and "enclose" smaller but more active silicon-carbon particles (smaller denominator), thereby optimizing the cycle life.
[0029] molecular This part represents the "stabilizing foundation" of the electrode. Among them... It is the mass fraction of graphite. This is the median particle size of graphite. Graphite itself has a stable structure and excellent cycling performance, which matches the "toughness" characteristic of the negative electrode during cycling. At the same time, in industrial applications, larger graphite particles (Dg) can sometimes maintain better structural integrity during repeated expansion and contraction, reducing the risk of cracking.
[0030] denominator This section represents the "source of activity" of the electrode and its "challenges". This directly corresponds to the net content of pure silicon in the electrode and is the main contributor to capacity. However, high activity implies enormous volume expansion pressure and internal stress. The median particle size of silicon-carbon materials... The reason this appears in the denominator is that the larger the silicon-carbon particles themselves are, the greater their absolute volume change during charging and discharging, which can easily lead to cracking and electrode structure collapse. Therefore, smaller silicon-carbon particle size is a basic requirement for long-life design.
[0031] Setting the cycle lifetime factor threshold to 1.5~4.0 can find a "golden window" with optimal overall performance between energy density and cycle lifetime, avoiding falling into the "capacity trap and lifetime trap".
[0032] When cycle life factor Less than 1.5 means that the denominator in the formula is less than 1.5. Relative to molecules Excessive silicon content directly leads to two serious consequences: ① Overly aggressive energy density surge, resulting in cycle collapse: This is usually accompanied by high A and B values. High silicon content can cause volume expansion exceeding 300%, triggering multi-scale failures ranging from SEI film rupture to electrode pulverization. ② The inherent instability of silicon-carbon: High Dsc values appear in the denominator, meaning that excessively large silicon-carbon particles become the "culprits of failure." Their huge volume changes during charge and discharge generate microcracks, leading to material pulverization and detachment, accelerating battery degradation. When the silicon content is greater than 30%, the capacity retention rate after 50 cycles is generally below 60%, far below the commercially required standard.
[0033] When cycle life factor A value greater than 4.0 means the numerator is much larger than the denominator. While this can improve cycle stability, it also presents the following problems: ① Low energy density: Low A and B values mean excessive use of low-capacity graphite. Graphite's theoretical specific capacity is only 372 mAh / g, far lower than silicon's 4200 mAh / g. Although this design has a long lifespan, it offers no advantage in battery performance. ② Inadequate "stabilizing" materials: In the formula, Dg is located in the numerator. If its value is too large, although it helps reduce electrode shrinkage stress, excessively large graphite particles may affect the diffusion path of lithium ions in the negative electrode, thus adversely affecting fast charging performance. This indicates that excessively pursuing cycle life can also lead to an imbalance in rate performance.
[0034] A first typical embodiment of the present invention provides a silicon-carbon / graphite composite negative electrode based on multi-parameter coupling optimization, comprising a negative electrode current collector and a negative electrode material loaded on one or both sides of the negative electrode current collector. The negative electrode material includes an active material, a conductive agent, and a binder; The active substances include silicon carbide materials and graphite; The conductive agent is a single-walled carbon nanotube (SWCNT). Meanwhile, by comparing the rate performance factor and cycle life factor calculated from the mass fraction of carbon silicon in the active material, the mass fraction of silicon in the carbon silicon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size (D50) of graphite, and the median particle size (D50) of silicon-carbon material with the set threshold, the mass fraction or median particle size is optimized.
[0035] In one or more embodiments, the negative electrode current collector comprises aluminum foil, copper foil, and titanium mesh, preferably copper foil. Copper foil exhibits excellent electrochemical stability, ensuring the long-term safety and reliability of the battery, while also possessing excellent conductivity and good mechanical properties.
[0036] In one or more embodiments, the binder comprises one or more of a composite system of polyacrylic acid, sodium alginate, polyimide, and sodium carboxymethyl cellulose (CMC) / styrene-butadiene rubber (SBR), preferably a sodium carboxymethyl cellulose / styrene-butadiene rubber composite system. The rigidity of CMC ensures the bond strength, while the flexibility of SBR provides volume buffering. The synergistic effect of the two greatly enhances the structural integrity of the electrode, preventing it from pulverizing and peeling off after repeated charge and discharge.
[0037] In one or more embodiments, the mass ratio of the active material, the conductive agent, and the binder is (94~98):(1~2):(2~3), preferably 96:1.5:2.5.
[0038] In one or more embodiments, the formula for calculating the rate performance factor using the mass fraction of carbon silicon in the active material, the mass fraction of silicon in the carbon silicon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size (D50) of graphite, and the median particle size (D50) of the silicon-carbon material is as follows: ; in, Indicates the rate performance factor; The mass fraction of carbon and silicon in the active material is 0. <A≤0.20; B represents the mass fraction of silicon in the silicon-carbon material, where 0.35 ≤ B ≤ 0.65. The value represents the mass fraction of single-walled carbon nanotubes in the negative electrode material, and 0.0004 ≤ C ≤ 0.001. The median particle size (D50) of graphite is given, and 5 μm ≤ Dg ≤ 15 μm. The median particle size (D50) of silicon-carbon materials is 3 μm ≤ ≤10 μm.
[0039] In one or more embodiments, the threshold value for the rate performance factor is set to 2000~8000.
[0040] To achieve ideal rate performance, multiple parameters are coupled and optimized by adjusting the material ratio and particle size distribution. Mass fraction of carbon and silicon in active materials Mass fraction of silicon element in silicon-carbon materials It is a provider of high-rate performance; therefore, the numerator of the rate performance factor RF is × Silicon is key to improving energy density; however, the higher its proportion, the more severe the volume expansion and structural instability of the material, which in turn impairs rate performance, making it a "high-risk" variable. The mass fraction of single-walled carbon nanotubes in the anode material... Median particle size of graphite Median particle size of silicon-carbon materials It is a high-rate performance restorer: the denominator of the rate performance factor RF is To offset the negative impact of the aforementioned "high-risk" variables, it is necessary to increase the mass fraction of the high-performance conductive agent SWCNT (single-walled carbon nanotubes). The larger the value, the smaller the rate performance factor (RF) value, indicating that more conductive agent is needed to build a high-quality conductive network; at the same time, the closer the particle size of graphite and silicon carbide, the more uniform the electrode stacking, and the less damage to rate performance.
[0041] Setting the threshold for the rate performance factor to 2000-8000 better balances the four objectives of energy density, rate performance, cycle stability, and cost control, making it the optimal choice for overall performance.
[0042] A rate performance factor (RF) below 2000 may result in poor rate performance. To achieve a low RF, high-capacity materials (A, B) are sacrificed, leading to insufficient total active material and directly limiting the upper limit of energy density. This may result in greater reliance on expensive conductive agents (high-performance conductive agent SWCNT) or stringent particle size requirements, leading to increased costs or significantly increased processing difficulty.
[0043] With a rate performance factor (RF) exceeding 8000, the cycle life is significantly shortened. Problems such as drastic volumetric failure due to high carbon silicon content, increased internal resistance due to increased silicon content, and uneven electrode structure caused by excessive particle size differences will all occur simultaneously. These factors combined lead to rapid capacity decay during battery cycling, increasing the risk of failure.
[0044] In one or more embodiments, the formula for calculating the cycle life factor using the mass fraction of carbon silicon in the active material, the mass fraction of silicon in the carbon silicon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size (D50) of graphite, and the median particle size (D50) of the silicon-carbon material is as follows: ; in, Indicates the cycle life factor; The mass fraction of carbon and silicon in the active material is 0. <A≤0.20; B represents the mass fraction of silicon in the silicon-carbon material, where 0.35 ≤ B ≤ 0.65. The value represents the mass fraction of single-walled carbon nanotubes in the negative electrode material, and 0.0004 ≤ C ≤ 0.001. The median particle size (D50) of graphite is given, and 5 μm ≤ Dg ≤ 15 μm. The median particle size (D50) of silicon-carbon materials is 3 μm ≤ ≤10 μm.
[0045] In one or more embodiments, the set threshold for the cycle life factor is 1.5 to 4.0.
[0046] To achieve the ideal cycle life, multiple parameters are coupled and optimized by adjusting the material ratio and particle size distribution. The core logic of the cycle life factor is to use a larger stable graphite phase (larger molecules) to "balance" and "enclose" smaller but more active silicon-carbon particles (smaller denominator), thereby optimizing the cycle life.
[0047] molecular This part represents the "stabilizing foundation" of the electrode. Among them... It is the mass fraction of graphite. This is the median particle size of graphite. Graphite itself has a stable structure and excellent cycling performance, which matches the "toughness" characteristic of the negative electrode during cycling. At the same time, in industrial applications, larger graphite particles (Dg) can sometimes maintain better structural integrity during repeated expansion and contraction, reducing the risk of cracking.
[0048] denominator This section represents the "source of activity" of the electrode and its "challenges". This directly corresponds to the net content of pure silicon in the electrode and is the main contributor to capacity. However, high activity implies enormous volume expansion pressure and internal stress. The median particle size of silicon-carbon materials... The reason this appears in the denominator is that the larger the silicon-carbon particles themselves are, the greater their absolute volume change during charging and discharging, which can easily lead to cracking and electrode structure collapse. Therefore, smaller silicon-carbon particle size is a basic requirement for long-life design.
[0049] Setting the cycle lifetime factor threshold to 1.5~4.0 can find a "golden window" with optimal overall performance between energy density and cycle lifetime, avoiding falling into the "capacity trap and lifetime trap".
[0050] when Less than 1.5 means that the denominator in the formula is less than 1.5. Relative to molecules Excessive silicon content directly leads to two serious consequences: ① Overly aggressive energy density surge, resulting in cycle collapse: This is usually accompanied by high A and B values. High silicon content can cause volume expansion exceeding 300%, triggering multi-scale failures ranging from SEI film rupture to electrode pulverization. ② The inherent instability of silicon-carbon: High Dsc values appear in the denominator, meaning that excessively large silicon-carbon particles become the "culprits of failure." Their huge volume changes during charge and discharge generate microcracks, leading to material pulverization and detachment, accelerating battery degradation. When the silicon content is greater than 30%, the capacity retention rate after 50 cycles is generally below 60%, far below the commercially required standard.
[0051] when A value greater than 4.0 means the numerator is much larger than the denominator. While this can improve cycle stability, it also presents the following problems: ① Low energy density: Low A and B values mean excessive use of low-capacity graphite. Graphite's theoretical specific capacity is only 372 mAh / g, far lower than silicon's 4200 mAh / g. Although this design has a long lifespan, it offers no advantage in battery performance. ② Inadequate "stabilizing" materials: In the formula, Dg is located in the numerator. If its value is too large, although it helps reduce electrode shrinkage stress, excessively large graphite particles may affect the diffusion path of lithium ions in the negative electrode, thus adversely affecting fast charging performance. This indicates that excessively pursuing cycle life can also lead to an imbalance in rate performance.
[0052] In one or more embodiments, the graphite includes one or more of artificial graphite and natural graphite.
[0053] A second typical embodiment of the present invention provides a lithium-ion battery comprising the silicon-carbon / graphite composite anode based on multi-parameter coupling optimization as described in the second aspect.
[0054] Example 1 1.1 A silicon-carbon / graphite composite anode based on multi-parameter coupling optimization, comprising a copper foil as a negative electrode current collector and a negative electrode material loaded on both sides of the copper foil as a negative electrode current collector; The negative electrode material includes active material, conductive agent and binder; The active material is composed of silicon carbide and graphite; the mass fraction of silicon carbide in the active material... The mass fraction of silicon in silicon-carbon materials is 10%. The median particle size of graphite is 50%. The median particle size of silicon-carbon materials is 10 μm. It is 5 μm; The conductive agent is single-walled carbon nanotubes (SWCNTs); the mass fraction of SWCNTs in the anode material is 0.07%. The binder is a sodium methyl cellulose (CMC) / styrene-butadiene rubber (SBR) composite system, with a mass ratio of sodium methyl cellulose (CMC) / styrene-butadiene rubber (SBR) of 1:1.5.
[0055] The mass ratio of active material, conductive agent and binder is 96:1.5:2.5.
[0056] 1.2 Preparation of silicon-carbon / graphite composite anode: The active material, conductive agent, and binder are obtained according to the conditions specified in section 1.1 for active material, conductive agent, and binder, respectively. The active material, conductive agent, and binder are mixed evenly and then coated onto both sides of the copper foil, with a coating density of 160 g / m² on both sides. 2 After drying, a silicon-carbon / graphite composite anode is obtained.
[0057] Example 2 2.1 A silicon-carbon / graphite composite negative electrode based on multi-parameter coupling optimization, comprising a negative electrode current collector copper foil and a negative electrode material loaded on both sides of the negative electrode current collector copper foil; The negative electrode material includes active material, conductive agent and binder; The active material is composed of silicon carbide and graphite; the mass fraction of silicon carbide in the active material... The mass fraction of silicon in silicon-carbon materials is 15%. The median particle size of graphite is 40%. The median particle size of silicon-carbon materials is 12 μm. It is 8 μm; The conductive agent is single-walled carbon nanotubes (SWCNTs); the mass fraction of single-walled carbon nanotubes in the anode material. It is 0.08%; The binder is a sodium methyl cellulose (CMC) / styrene-butadiene rubber (SBR) composite system, with a mass ratio of sodium methyl cellulose (CMC) / styrene-butadiene rubber (SBR) of 1:1.5.
[0058] The mass ratio of active material, conductive agent and binder is 96:1.5:2.5.
[0059] 2.2 Preparation of silicon-carbon / graphite composite anode: The active material, conductive agent, and binder are obtained according to the conditions specified in section 2.1 for active material, conductive agent, and binder, respectively. The active material, conductive agent, and binder are mixed evenly and then coated onto both sides of the copper foil, with a coating density of 160 g / m² on both sides. 2 After drying, a silicon-carbon / graphite composite anode is obtained.
[0060] Example 3 3.1 A silicon-carbon / graphite composite negative electrode based on multi-parameter coupling optimization, comprising a negative electrode current collector copper foil and a negative electrode material loaded on both sides of the negative electrode current collector copper foil; The negative electrode material includes active material, conductive agent and binder; The active material is composed of silicon carbide and graphite; the mass fraction of silicon carbide in the active material... The mass fraction of silicon in silicon-carbon materials is 8%. The median particle size of graphite is 60%. The median particle size of silicon-carbon materials is 8 μm. It is 4 μm; The conductive agent is single-walled carbon nanotubes (SWCNTs); the mass fraction of SWCNTs in the anode material is 0.05%. The binder is a sodium methyl cellulose (CMC) / styrene-butadiene rubber (SBR) composite system, with a mass ratio of sodium methyl cellulose (CMC) / styrene-butadiene rubber (SBR) of 1:1.5.
[0061] The mass ratio of active material, conductive agent and binder is 96:1.5:2.5.
[0062] 3.2 Preparation of silicon-carbon / graphite composite anode: The active material, conductive agent, and binder are obtained according to the conditions specified in section 3.1 for active material, conductive agent, and binder, respectively. The active material, conductive agent, and binder are mixed evenly and then coated onto both sides of the copper foil. The surface density of the coating is 160 g / m² on both sides. 2 After drying, a silicon-carbon / graphite composite anode is obtained.
[0063] Comparative Example 1 This comparative example provides a silicon-carbon / graphite composite negative electrode, including a negative electrode current collector copper foil and a negative electrode material loaded on both sides of the negative electrode current collector copper foil; The negative electrode material includes active material, conductive agent and binder; The active material is composed of silicon carbide and graphite; the mass fraction of silicon carbide in the active material... The mass fraction of silicon in silicon-carbon materials is 25%. The median particle size of graphite is 50%. The median particle size of silicon-carbon materials is 10 μm. It is 5 μm; The conductive agent is single-walled carbon nanotubes (SWCNTs); the mass fraction of SWCNTs in the anode material is 0.07%. The binder is a sodium methyl cellulose (CMC) / styrene-butadiene rubber (SBR) composite system, with a mass ratio of sodium methyl cellulose (CMC) / styrene-butadiene rubber (SBR) of 1:1.5.
[0064] The mass ratio of active material, conductive agent and binder is 96:1.5:2.5.
[0065] The preparation method of the silicon-carbon / graphite composite negative electrode is the same as in Example 1.
[0066] Comparative Example 2 This comparative example provides a silicon-carbon / graphite composite negative electrode, including a negative electrode current collector copper foil and a negative electrode material loaded on both sides of the negative electrode current collector copper foil; The negative electrode material includes active material, conductive agent and binder; The active material is composed of silicon carbide and graphite; the mass fraction of silicon carbide in the active material... The mass fraction of silicon in silicon-carbon materials is 10%. The median particle size of graphite is 50%. The median particle size of silicon-carbon materials is 18 μm. It is 15μm; The conductive agent is single-walled carbon nanotubes (SWCNTs); the mass fraction of SWCNTs in the anode material is 0.02%. The binder is a sodium methyl cellulose (CMC) / styrene-butadiene rubber (SBR) composite system, with a mass ratio of sodium methyl cellulose (CMC) / styrene-butadiene rubber (SBR) of 1:1.5.
[0067] The mass ratio of active material, conductive agent and binder is 96:1.5:2.5.
[0068] The preparation method of the silicon-carbon / graphite composite negative electrode is the same as in Example 1.
[0069] The rate performance factor and cycle life factor of each negative electrode in Examples 1-3 and Comparative Examples 1-2 were calculated according to the formulas for rate performance factor and cycle life factor, respectively, and the results are shown in Table 1.
[0070] Table 1. Rate performance factor and cycle life factor of each negative electrode in Examples 1-3 and Comparative Examples 1-2
[0071] Experimental Example 1 To further verify that the silicon-carbon / graphite composite anode based on multi-parameter coupling optimization has both excellent cycle performance and rate performance, this experiment tested the performance of lithium-ion batteries containing the anodes of Examples 1-3 and Comparative Examples 1-2.
[0072] The conventional positive electrode formulation of NCM811, a commercially available ternary material for lithium-ion batteries, was used to assemble a pouch cell with a nominal capacity of 3Ah by combining the negative electrode, positive electrode, separator, and electrolyte.
[0073] The test results are shown in Table 2.
[0074] Table 2 Performance Test Results
[0075] As shown in Table 2, Examples 1-3, which strictly meet the constraints of the rate performance factor (RF) and cycle life factor (CLF) proposed in this invention, all exhibit excellent rate performance and cycle life while maintaining high capacity. Comparative Example 1 (with an excessively high silicon-carbon ratio, resulting in both RF and CLF exceeding the optimization range) showed the highest initial capacity, but its rate and cycle performance deteriorated significantly. Comparative Example 2 (with insufficient CNT content and excessively large graphite particle size) exhibited poor rate and cycle performance. This fully demonstrates the effectiveness and necessity of the multi-parameter coupling relationship proposed in this invention for synergistically optimizing battery performance.
[0076] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A silicon-carbon / graphite composite anode based on multi-parameter coupling optimization, characterized in that, Includes negative electrode current collector and negative electrode material loaded on one or both sides of the negative electrode current collector; The negative electrode material includes an active material, a conductive agent, and a binder; The active substances include silicon carbide materials and graphite; The conductive agent is a single-walled carbon nanotube; Simultaneously, by comparing the calculated rate performance factor and cycle life factor with the set thresholds based on the mass fraction of carbon silicon in the active material, the mass fraction of silicon in the carbon silicon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size of graphite, and the median particle size of silicon-carbon material, each mass fraction or median particle size is optimized.
2. The silicon-carbon / graphite composite anode based on multi-parameter coupling optimization as described in claim 1, characterized in that, The negative electrode current collector includes aluminum foil, copper foil, and titanium mesh, preferably copper foil.
3. The silicon-carbon / graphite composite anode based on multi-parameter coupling optimization as described in claim 1, characterized in that, The binder includes one or more of the following: polyacrylic acid, sodium alginate, polyimide, sodium carboxymethyl cellulose (CMC) / styrene-butadiene rubber (SBR) composite system, preferably sodium carboxymethyl cellulose / styrene-butadiene rubber composite system.
4. The silicon-carbon / graphite composite anode based on multi-parameter coupling optimization as described in claim 1, characterized in that, The mass ratio of active material, conductive agent and binder is (94~98):(1~2):(2~3), preferably 96:1.5:2.
5.
5. The silicon-carbon / graphite composite anode based on multi-parameter coupling optimization as described in claim 1, characterized in that, The formula for calculating the rate performance factor using the mass fraction of carbon and silicon in the active material, the mass fraction of silicon in the carbon-silicon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size (D50) of graphite, and the median particle size (D50) of silicon-carbon material is as follows: ; in, Indicates the rate performance factor; The mass fraction of carbon and silicon in the active material is 0. <A≤0.20; B represents the mass fraction of silicon in the silicon-carbon material, where 0.35 ≤ B ≤ 0.
65. The value represents the mass fraction of single-walled carbon nanotubes in the negative electrode material, and 0.0004 ≤ C ≤ 0.
001. The median particle size (D50) of graphite is given, and 5 μm ≤ Dg ≤ 15 μm. The median particle size (D50) of silicon-carbon materials is 3 μm ≤ ≤10 μm.
6. The silicon-carbon / graphite composite anode based on multi-parameter coupling optimization as described in claim 1, characterized in that, The threshold for setting the rate performance factor is 2000~8000.
7. The silicon-carbon / graphite composite anode based on multi-parameter coupling optimization as described in claim 1, characterized in that, The formula for calculating the cycle life factor using the mass fraction of carbon and silicon in the active material, the mass fraction of silicon in the carbon-silicon material, the mass fraction of single-walled carbon nanotubes in the anode material, the median particle size (D50) of graphite, and the median particle size (D50) of silicon-carbon material is as follows: ; in, Indicates the cycle life factor; The mass fraction of carbon and silicon in the active material is 0. <A≤0.20; B represents the mass fraction of silicon in the silicon-carbon material, where 0.35 ≤ B ≤ 0.
65. The value represents the mass fraction of single-walled carbon nanotubes in the negative electrode material, and 0.0004 ≤ C ≤ 0.
001. The median particle size (D50) of graphite is given, and 5 μm ≤ Dg ≤ 15 μm. The median particle size (D50) of silicon-carbon materials is 3 μm ≤ ≤10 μm.
8. The silicon-carbon / graphite composite anode based on multi-parameter coupling optimization as described in claim 1, characterized in that, The set threshold for the cycle life factor is 1.5 to 4.
0.
9. The silicon-carbon / graphite composite anode based on multi-parameter coupling optimization as described in claim 1, characterized in that, The graphite includes one or more of artificial graphite and natural graphite.
10. A lithium-ion battery, characterized in that, It includes the silicon-carbon / graphite composite anode based on multi-parameter coupling optimization as described in any one of claims 1 to 9.